Identification and Validation of Ferroptosis-Related LncRNA Signatures as a Novel Prognostic Model for Colon Cancer - Wu, Zhiwei; Lu, Zhixing; Li, Liang; Ma, Min; Long, Fei; Wu, Runliu; Huang, Lihua; Chou, Jing; Yang, Kaiyan; Zhang, Yi; Li, Xiaorong; Hu, Gui; et al. (Frontiers in Immunology, 2022)
Abstract Background: Ferroptosis is a newly defined form of programmed cell death that plays an important role in many cancers. However, ferroptosis-related lncRNAs involved in the regulation of colon cancer are not thoroughly understood. This study aimed to identify a prognostic ferroptosis-related lncRNA signature in colon cancer and explore its potential molecular function. Methods: RNA-seq data and relevant clinical information were obtained from The Cancer Genome Atlas (TCGA) database, and a list of ferroptosis-related genes was extracted from the FerrDb website. Analysis of differentially expressed ferroptosis-related lncRNAs was screened through the ‘limma’ package in R software. By implementing coexpression analysis and Univariate cox analysis, we then identified prognostic ferroptosis-related lncRNAs. Using Cox regression analysis with the least absolute shrinkage and selection operator (LASSO) algorithm, we constructed a prognostic model based on 4 ferroptosis-related lncRNAs. We evaluated the prognostic power of this model using Kaplan–Meier (K-M) survival curve analysis and receiver operating characteristic (ROC) curve analysis. Moreover, the relationships between the signature and immune landscape, somatic mutation and drug sensitivity were further explored. Finally, in vitro experiments were conducted to validate the functions of AP003555.1 and AC000584.1. Results: A 4-ferroptosis-related lncRNA signature was constructed. Two risk groups were classified based on the risk score calculated by this signature. The signature-based risk score exhibited a more powerful capacity for survival prediction than traditional clinicopathological features in colon patients. Additionally, we observed a significant difference in immune cells such as CD8+ T cells or macrophages between the two groups. Moreover, the high-risk group exhibited lower IC50 values for some chemotherapy drugs, such as cisplatin, docetaxel, bleomycin or axitinib. Finally, the in vitro experiment showed that the processes of ferroptosis were suppressed after AP003555.1 and AC000584.1 knockdown. Conclusion: The proposed 4-FRL signature is a promising biomarker to predict clinical outcomes and therapeutic responses in colon patients.